Controversies related to the use of agents with a potential anticancer activity - Wysocki, Piotr J.; Mackiewicz, Andrzej (Contemporary Oncology/Współczesna Onkologia, 2006)
Discoveries of antitumoral potential of commonly used, non-oncological drugs have appeared regularly in the medical journals all over the years. Information on such agents as statins, COX-2 inhibitors or inhibitors of ACE have been always widely discussed by oncologist. Despite numerous proofs of their antitumoral activity obtained from preclinical and retrospective cohort studies to date only few prospective, randomized clinical studies have been performed. Moreover, only few of these clinical studies have confirmed the expected prophylactic or therapeutic effect of the tested agents in relation to neoplastic diseases. Based on preclinical and retrospective cohort studies one assumes that ACE inhibitors impair development of experimental tumors and decrease the relative risk of cancer. The antitumoral mechanism of ACE inhibitors is believed to be associated with a blockade of proliferation and induction of apoptosis of tumor cells as well as with inhibition of neoangiogenesis. In our studies we have evaluated the effect of captopril (ACE inhibtor) on growth and development of immunogenic tumors in murine models of renal cell cancer (RenCa) and metylocholantrene-induced sarcoma (MehtA). Suprisingly, we have demonstrated that captopril promoted growth and metastatic potential of tumor cells and shortened the survival of tumor-bearing mice with an intact immune system. The observed effect was associated with an impairment of specific cellular anti-tumor responses mediated by cytotoxic T lymphocytes (CD8+). Our studies further confirm the common opinion that administration of drugs with a suspected anti-tumor activity must be based on tightly controlled, prospective and randomized clinical studies.